التشكيل الكاليغرافي عند نزار قباني ، تأسيس لكتابة بصرية جديدة - تاوريريت, نبيلة (University of El-oued, 2021)
سيتم التركيز في هذا المقال على تحولات الخطاب الشعري في ديباجته المعاصرة ، ديباجة مختلفة عما كان مألوفا ، تظهر في البناء الهندس ي للقصيدة ، الذي حفل بتشكيلات كاليغرافية عصرية متعددة ، يسعى الشاعر من خلالها إلى تأسيس كتابة بصرية جديدة تنفعل مع العصر الراهن وتهتم بقضايا الإنسان ، وكذا البحث عن حقائق الذات العربية. In this article, the focus will be on the shifts in poetic discourse in its contemporary preamble, a different preamble from what was familiar, appearing in the geometrical structure of the poem, which was celebrated with multiple modern formations, through which the poet seeks to establish a new visual writing that reacts with the current era and is concerned with human issues, as well as Searching for the facts of the Arab self.
Kaligraphic composition according to Nizar Qabbani, a foundation for a new visual writing
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: التشكيل، الكاليغراف، الكتابة ، القصيدة المعاصرة، البصري، التحول.; Diacritics, calligraphy, writing, contemporary poem, visual, metamorphosis.